Piercing the Corporate Veil on the Responsibilities of Limited Liability Company Directors in Nominee Agreements which have the Potential Risk of Lawsuits - Rizka Rahadiyani Aisyah; Arman Nefi (STMIK Dharma Wacana, 2023)
Companies are also an important business component and are widely available in the world, including in Indonesia where they are legal entities. The integrity of a member of the company's board of directors and board of commissioners to maintain their loyalty as the party entrusted with managing the company properly and correctly as a responsibility to stakeholders. This action is known as the Piercing the Corporate Veil doctrine, which in this paper is at issue if it turns out that there is a nominee agreement between the directors and shareholders of a third party who is actually the party who is one of the shareholders and what is the potential risk of legal action? If a dispute occurs in the company due to the nominee agreement, the company will experience the risk of loss. The author researches with normative legal research, which involves studying documents or written data, research on legal systematics, legal theory. In the initial stage the author conducted research on documents related to the subject of this discussion. Apart from that, use is based on the internet, newspapers and electronic media. In this case, the action of Piercing the Corporate Veil Shareholders in a Limited Liability Company turns out to be the discovery of a nominee agreement between the directors and shareholders from a third party who is actually the party who is one of the shareholders, so in this case the Nominee Agreement can be null and void by law and an attempt to smuggle the law because the Nominee Agreement has violated several regulations in Indonesia, namely Article 33 of the Investment Law and Article 1320 of the Civil Code and is not valid. The potential risk of a company lawsuit if a dispute occurs is due to the nominee agreement which results in the company experiencing a risk of loss because seen from the position of the Piercing the Corporate Veil Doctrine, it cannot be implemented properly because the agreement between shareholders and directors has been violated. regulations in Indonesia, namely Article 33 of the Investment Law and Article 1320 of the Civil Code. So there is less accountability.